Effects of the Top Edge Impedance on Sound Barrier Diffraction - Xiaofan Huang; Haishan Zou; Xiaojun Qiu (Applied Sciences, 2020)
Sound barriers can be configured with different top edge impedance to improve their noise control performance. In this paper, the integral equation method was used to calculate the sound field of a barrier with various top edge impedance, and the effects of the barrier top edge impedance on sound barrier diffraction were investigated. The simulation results showed that the noise reduction performance of a sound barrier with a soft boundary on its top edge was larger than that with a hard boundary, but there were some impedance values which, if assigned to the top edge boundary, would give the sound barrier even better noise reduction performance. It was found that the sound barrier with a good top edge impedance formed a dipole-like radiation pattern above the barrier to expand the effective range of the shadow zone. The research discoveries reported in this paper point out the potentials of using acoustics metamaterials or active control methods to implement the desired good impedance on the top edge of a sound barrier for better noise reduction.